EFFECT OF MENSTRUAL CYCLE WITH BLOOD GLUCOSE LEVELS - Primadina, Meka Anggidian (Majority, 2015)
Abstract The early or young adulthood is one of stages from life cycle in the range of age between 19 to 40. In this stage there will be a process of growth maturation and development both physically and psychologically. The physical growth maturation and developmet include by various organs, one of them is reproductive organ. In this stage, reproductive health is very important because it is closely related to fertility level. Menstrual disorders are important indocators that indicate the impairment of reproductive fuction that can be associated with the increased of various diseases such as cervical cancer, breast cancer, infertility, diabetes mellitus (DM) and drugs or the use of alternative medicines like herbal medicines. Some of factors that can cause menstrual cycle disorders such as hormonal disorders, growth of reproductive organs, nutrirional status, stress, age and metabiloc deseases lile diabetes mellitus (DM). Keywords:DiabetesMellitus(DM) type 2, GlucoseBlood, Insulin, and Menstrual Cycle Abstrak Masa dewasa awal atau muda merupakan salah satu tahap dari siklus kehidupan dengan rentang usia 19-40 tahun. Pada tahap ini terjadi proses pematangan pertumbuhan dan perkembangan baik secara fisik maupun psikologis. Pematangan pertumbuhan dan perkembangan secara fisik ini meliputi berbagai organ, salah satunya yaitu organ reproduksi. Kesehatan reproduksi pada tahap ini sangatlah penting karena berkaitan erat dengan tingkat fertilitas. Gangguan menstruasi merupakan indicator penting yang menunjukkan adanya gangguan fungsi system reproduksi yang dapat dihubungkan dengan peningkatan risiko berbagai penyakit seperti kanker rahim, kanker payudara, infertilitas, diabetes mellitus (DM) dan obat-obatan atau penggunaan obat alternatif seperti pengobatan herbal. Beberapa faktor yang dapat menyebabkan ganguan siklus menstruasi antara lain gangguan hormonal, pertumbahan organ reproduksi, status gizi, stress, usia dan penyakit metabolic seperti diabetes mellitus (DM). Kata Kunci: Siklus Menstruasi, Insulin, Diabetes Mellitus (DM) tipe 2, Glukosa Darah